Out of sight but not out of mind: Home countries’ macroeconomic volatilities and immigrants’ mental health - Nguyen, Ha Trong; Connelly, Luke (My University, 2018)
We provide the first empirical evidence that better economic performances by immigrants' countries of origin, as measured by lower consumer price index (CPI) or higher gross domestic product, improve immigrants' mental health. We use an econometrically‐robust approach that exploits exogenous changes in macroeconomic conditions across immigrants' home countries over time and controls for immigrants' observable and unobservable characteristics. The CPI effect is statistically significant and sizeable. Furthermore, the CPI effect diminishes as the time since emigrating increases. By contrast, home countries' unemployment rates and exchange rate fluctuations have no impact on immigrants' mental health.
Health Economics
Keywords: Finance; Culture -- Immigrants; Health -- Mental; Health and wellbeing; Income, wealth and finances; Migration and settlement; Finance; Health; Culture; Mental; Immigrants; Migration and settlement; Health and wellbeing; Income, wealth and finance